Note on the Application of Transient Wave Packets for Wave–Ice Interaction Experiments - Marco Klein; Moritz Hartmann; Franz von Bock und Polach (Water, 2021)
This paper presents the transient wave packet (TWP) technique as an efficient method for wave–ice interaction experiments. TWPs are deterministic wave groups, where both the amplitude spectrum and the associated phases are tailor-made and manipulated, being well established for efficient wave–structure interaction experiments. One major benefit of TWPs is the possibility to determine the response amplitude operator (RAO) of a structure in a single test run compared to the classical approach by investigating regular waves of different wave lengths. Thus, applying TWPs for wave–ice interaction offers the determination of the RAO of the ice at specific locations. In this context, the determination of RAO means that the ice characteristics in terms of wave damping over a wide frequency range are obtained. Besides this, the wave dispersion of the underlying wave components of the TWP can be additionally investigated between the specific locations with the same single test run. For the purpose of this study, experiments in an ice tank, capable of generating tailored waves, were performed with a solid ice sheet. Besides the generation of one TWP, regular waves of different wave lengths were generated as a reference to validate the TWP results for specific wave periods. It is shown that the TWP technique is not only applicable for wave–ice interaction investigations, but is also an efficient alternative to investigations with regular waves.